The Current Health of Metropolitan Labour Markets in the United States. (1st July 2015) - Mulligan, Gordon F.; Reid, Neil; Moore, Michael S.
Abstract: Much recent research on US labour markets has turned to tracing out the dramatic changes that accompanied and followed the events of the Great Recession (2007–2009). But to date this research has led to more temporal as opposed to spatial detail about those changes. This paper uses an online data set to assess the relative economic health (performance) of the US's more than 350 metropolitan labour markets during and after the Great Recession. These data address both the current level (e.g. unemployment rate) and the recent trend (e.g. 3‐year job growth) in the economic health of those labour markets. Multivariate analysis generates one sub‐index for level and a second sub‐index for trend and then an overall performance index is calculated. But, after recognising that heterogeneity in these labour markets exists according to their different sizes, this paper re‐examines those online data using four separate population size classes. New indices are then generated reflecting the relative sizes of the metropolitan labour markets and the new rankings that follow differ in important ways from the original rankings. The findings also indicate a disjuncture now exists between the economic health of Snowbelt versus Sunbelt cities. Coming immediately out of the Great Recession the average economic health of Northern cities is much better than that of Southern cities.